Measurement of the scCO2 Storage Ratio for the CO2 Reservoir Rocks in Korea. (November 2016) - Wang, Sookyun; Kim, Jungtaek; Lee, Minhee
Abstract: Based on the lab experiments, the average scCO2 storage ratio of the Janggi conglomerate was calculated at 31.2%, which can be used to evaluate the feasibility of the Janggi basin as a scCO2 storage site in Korea. Assuming that the average radius of the CO2 storage formations is 250 m and the average thickness of the formations under 800 m in depth is 50 m, the scCO2 storage capacity of the Janggi basin is larger than 400, 000 tons, demonstrating that the Janggi basin has a great potential for use as a pilot scale test site for the CO2 storage.